Promosi Geopark Merangin melalui Event Manifesto Art and Edutainment - Sari, Intan Purnama; Chaerowati, Dede Lilis; Mulyana, Dadan; Agus, Agus; Misnawati, Misnawati (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
When the Covid-19 pandemic caused the number of visitors to the Geopark to decline, the Merangin Geopark Management Board made a breakthrough by holding the Geopark Manifesto Art & Edutainment Event since 2022 and promoting it to attract tourists. This article aims to find out the management of event promotion. Using a qualitative research method with a case study approach, this study conducted interviews, literature studies, and documentation to dig deeper into the data. The research subjects were determined by purposive sampling with key informants being Geopark Management Agency staff and supporting informants. The data analysis technique uses the Miles and Huberman Model. Data validity test using source triangulation. The results showed that event promotion management was carried out through a series of stages including research, design, planning, coordination, and evaluation. Promotion on Instagram uses invitation sentences and interesting videos. Regional Culture Week is a unique event by combining elements of culture, education, and art. The conclusion of the research is that the management of Merangin Geopark promotion applies an event management approach, Instagram management pays attention to the elements of Chris Heuer's 4C Framework, and event collaboration with regional cultural weeks as an event marketing strategy.